THE OBLIGATORY MOVES OF BACKGROUND SECTION IN RESEARCH PROPOSAL INTRODUCTIONS : An Analysis of Undergraduate Students' Research Proposals in English Education Program - Zakiah, Siti (2015)
This study aims to investigate the obligatory moves of students' research proposal introduction. This study used a descriptive study, particularly text analysis. The participants of this study were last semester undergraduate students of English study program at one public university in Bandung. This study employed four data collection techniques; research site, population, sample of the study, and research instrument. The data were, then, analyzed based on the theory of Swales' CARS (Create a Research Space) model of introduction (1990, 1994, and 2008). The result shows that among 50 background section of research proposal introductions there are only 15 background section of research proposal introductions that incorporate the three obligatory moves of introduction. Besides, the occurrences of each obligatory moves has their own proportion. The most common moves was stating the previous research (M-1c) with 46 occurrences (61%). While the indication of gap/ niche based on previous research that has been stated before (M-2) and the statement of purpose of the research that will be conducted based on the gap (M-3a) became the least common move with each of the occurrences was 15 (20%). Although there were background sections that also incorporated the niche or indication of gap, but those are not stated based on the previous research. These niches were stated based on the reality or justification of environmental situations of the conducting research. Keywords: Research Proposal Introduction, Background, CARS model. Penelitian ini bertujuan untuk menganalisis move atau elemen wajib yang terdapat dalam latar belakang pendahuluan proposal penelitian mahasiswa program studi pendidikan bahasa Inggris. Penelitian ini menggunakan deskriptif kualitatif, terutama analisis teks. Penelitian ini mengikutsertakan mahasiswa semester akhir dari program studi bahasa Inggris di salah satu universitas negeri di kota Bandung. Penelitian ini menggunakan empat teknik pengumpulan data; tempat atau situs penelitian, populasi, sampel penelitian, dan instrument penelitian. Data yang diperoleh kemudian dianalisis berdasarkan teori CARS (Create a Research Space) dalam pendahuluan oleh John M. Swales (1990, 1994, 2008). Hasil penelitian menunjukkan bahwa dari 50 latar belakang pendahuluan proposal penelitian hanya terdapat 15 latar belakang pendahuluan proposal penelitian yang menyertakan tiga move atau langkah wajib pendahuluan. Selain itu, masing- masing move wajib memiliki proporsi kemunculan atau kejadian masing- masing dari 50 latar belakang yang ada. Move atau langkah yang paling umum muncul adalah pernyataan penelitian sebelumnya (M-1c) dengan kejadian sebanyak 46 kali (61%). Sedangkan pernyataan kesenjangan/ relung atau gap (M-2) berdasarkan penelitian sebelumnya dan pernyataan tujuan dari penelitian yang akan dilakukan berdasarkan kesenjangan/ relung yang telah ditemukan (M-3a) menjadi langkah yang paling sedikit muncul dengan masing- masing kejadian sebanyak 15 kali (20%). Meskipun ada latar belakang yang juga menyertakan gap atau indikasi kesenjangan, tetapi gap tersebut tidak dinyatakan berdasarkan penelitian sebelumnya. Relung atau gap itu dinyatakan berdasarkan realitas atau justifikasi dari situasi realitas penelitian yang akan dilakukan. Kata kunci: Pendahuluan Proposal Penelitian, Latar Belakang, Model CARS.